Vesicle–tube–ribbon evolution via spontaneous fusion in a self-correcting supramolecular tissue. Issue 42 (8th June 2015) - Yu, Xudong; Zhang, Ping; Li, Yajuan; Chen, Liming; Yi, Tao; Ma, Zichuan
Abstract : A reversible vesicle–tube–fibre transition was monitored in a cholesterol-based assembly with self-healing and self-correcting characteristics. Abstract : A real-time reversible fusion pathway from vesicles to fibres, passing through several types of intermediates such as fused vesicles and short and long tubes, was monitored in a cholesterol-based assembly. The mechanism of the structural evolution via a gelation process was studied by means of electronic microscopy, small-angle X-ray scattering and powder X-ray diffraction. The fibres of the gel tissue could be switched by sonication and mechanical shaking to tubes and broken fibres, respectively, and reversed by thermal treatment or aging for a certain period via a fusion process. The destroyed fibres could match with each other in the healing process, showing the self-healing and self-correcting character of the self-assembly. This complete investigation of the reversible vesicle–tube–ribbon transition is of great significance in the design and synthesis of new nano/microstructures, especially stimulus-responsive aggregates through a "bottom-up" strategy.